108 A public health intervention program to improve the initial management of soft tissue sarcomas. (23rd September 2015) - Bellera, C; Bui, B N; Chevreau, C; Bauvin, E; Pélissier, F; Grosclaude, P; Savès, M; Bompas, E; Albert, Sabrina; Mathoulin-Pélissier, S
Abstract : Context: Soft tissue sarcomas (STS) are rare tumours. In France, STS is estimated to represent about 1% of all cancers, the true incidence of which remains unknown. Management of STS is particularly difficult due to the initial diagnosis which is complex (more than 50 histological subtypes). Moreover, initial surgery is often inappropriate as surgery is usually performed before biopsy resulting in complex decisions once STS is histological proven. Objectives: A quasi-experimental before/after study (with control region) was implemented to set up and evaluate a public health intervention aimed at improving the quality of the initial management of STS (diagnosis and surgery). Additional objectives involved measuring the impact of this intervention, exploring factors associated in variations in the quality of STS management, and estimating STS incidence rate. Program: The program was implemented in collaboration with the French Sarcoma Group (FSG), regional cancer registries and cancer regional networks. It involves five regions (covering 20% of the French population). This study was initiated in November 2006 and involves three phases. In the first phase (November 2006 to December 2007), information on STS cases diagnosed during this period was collected. Between January 2008 and October 2008, the public health program was implemented in four regions (the fifth region serves as a control), and involved two distinct actions: (1) written information campaign directed towards all relevant practitioners, and (2) oral communications in dedicated meetings by opinion leaders. Finally, information on STS cases diagnosed after this 'action' period was collected. Based on available incidence data, we anticipated that 300 STS cases per year would be recruited. As we were interested in evaluating the quality of STS management before and after the program, a preliminary step involved validating quality indicators (QIs) for cancer care. As such, we assessed which QIs were the most relevant to evaluate the quality of the management of STS. To validate QIs, a Delphi consensus method was set up. Based on Good Clinical Practices and a literature review, we prepared a set of 25 QIs, and relied on a panel of advisory FSG experts (n=19) from multiple medical specialities. We chose to measure the main impact of both actions (diagnosis + surgery) using a composite criterion focussing on three steps of initial management (imaging diagnosis, surgery, and multidisciplinary meeting), since these are directly associated with survival. Results in Terms of Clinical Impact: Regarding QIs, consensus was reached for 23 items, with perfect consensus for 9 QIs (eg, the need for multidisciplinary management teams, appropriate surgical biopsy techniques). During the actions phase in the four concerned regions (one region was the control) about 16 000 written information (in the form of one double-sided page) were sent to practitioners; 18 meetings allowed us to increase awareness of about 500 practitioners. One month before the end of the study, a total of 858 cases were already included in five region (420 in the 'before' phase). As a preliminary result, we could measure the main endpoint (the quality of STS management based on the composite criterion) in one region (210 cases). Data suggest an absolute increase of 10% (50% relative increase) in the quality of the initial management of STS. Moreover, preliminary data based on two regions (269 cases) in 2007 show that the incidence rate standardised on the French population was 4.14 cases per 100 000 inhabitants (4.03/100 000 when standardised on European population). Discussion (Perspectives) and Conclusions: Preliminary findings suggest an underestimation of STS incidence. The relevant QIs will be used to evaluate the public health program which will allow us to (1) obtain a picture of the current practices in the management of STS patients; (2) assess if simple actions can improve practices. Our results need to be confirmed with complete data from all regions where the program was implemented and to be compared to the control region. In 2010, a clinical and pathological sarcoma network will be implemented in France (rare tumour network supported by French national institute) and our final results will be relevant for national actions in STS management.    Contexte: Les sarcomes des tissus mous (STM) sont des tumeurs rares. En France, ils représentent approximativement 1% des cancers, bien que l'incidence réelle demeure méconnue. Leur prise en charge est particulièrement difficile en raison du diagnostic initial complexe (plus de 50 sous-types histologiques). De plus, la chirurgie initiale est souvent inappropriée puisqu'une chirurgie est souvent réalisée avant même la biopsie, rendant le processus décisionnel beaucoup plus complexe une fois que le diagnostic de STM est posé. Objectifs: Une étude quasi-expérimentale avant/après soutenue par un financement national a été mise en place afin de développer une intervention de santé publique visant à améliorer la qualité de la prise en charge initiale des sarcomes (diagnostic + chirurgie). Les objectifs secondaires concernent l'évaluation de l'impact de cette intervention, l'exploration des facteurs associés aux variations de la qualité de la prise en charge des STM, et l'estimation de l'incidence des STM. Programme: Le programme a été mis en place en collaboration avec le Groupe Sarcome Français (GSF), les registres de cancer régionaux, et les réseaux régionaux de cancérologie. Cinq régions sont concernées (20% de la population française). L'étude a débuté en 11/2006 et impliquait 3 phases. Dans la première phase (11/2006-12/2007), les informations relatives aux STM inclus durant cette période ont été recueillies. Entre 01/2008 et 10/2008, le programme de santé publique a été mis en place dans 4 régions (la 5è servant de contrôle), comprenant 2 actions distinctes:une campagne d'information écrite envoyée à tous les praticiens concernés, et des communications orales par des leaders d'opinion au cours de réunions dédiées. Enfin, les informations relatives aux STM diagnostiqués après cette phase d'actions ont été recueillies. Nous avons estimé qu'environ 300 cas de STM/an seraient inclus. Puisque nous nous intéressions à l'évaluation de la qualité de la prise en charge des STM, nous avons dans une étape préliminaire, validé des indicateurs de qualité (IQ) de prise en charge du cancer, en particulier pour les STM. Afin de valider ces IQ, nous nous sommes basés sur la méthode de consensus explicite de type Delphi. A partir des référentiels de bonnes pratiques et une revue de la littérature, nous avons présélectionné 25 IQ ainsi qu'un panel pluridisciplinaire d'experts du GSF (n=19). Nous avons évalué l'impact du programme en termes de qualité du diagnostic et de la chirurgie à partir d'un critère composite spécifique à 3 étapes clés de la prise en charge initiale (imagerie au diagnostic, chirurgie, réunion de concertation pluridisciplinaire), ces 3 éléments étant associés à la survie. Resultats en terme d'impacts clinique: Le recueil des données sera complété en décembre 2009. Concernant les IQ, un consensus a été atteint pour 23 items, dont un consensus parfait pour 9 IQ (ex: besoin d'équipes pluridisciplinaires ou de techniques de biopsie appropriées). Au cours de la phase 'Actions', environ 16, 000 documentations écrites (une page recto-verso) ont été envoyées aux praticiens concernés, et 18 communications orales ont été réalisées afin d'améliorer la connaissance d'environ 500 praticiens. Un mois avant la fin de l'étude, 858 cas de STM ont été inclus (420 pour la phase avant). A titre de résultat préliminaire, nous avons pu mesurer le critère principal (critère composite) dans l'une des 5 régions (210 cas). Les données suggèrent une augmentation absolue de 10% (augmentation relative de 50%) de la qualité de la prise en charge initiale des STM et une incidence standardisée (population France) de 4.14/100 000 (4.03/100 000 lorsque standardisation sur l'Europe). Discussion et conclusions: les résultats préliminaires suggèrent une sous-estimation de l'incidence des STM. Les IQ concernés seront utilisés afin de valider ce programme permettant 1) d'obtenir une photographie des pratiques actuelles dans la prise en charge des STM;2) d'évaluer si des actions simples peuvent améliorer les pratiques;3) d'estimer le taux d'incidence des STM dans 5 régions de France. Nos résultats doivent être confirmés par les données complètes des 5 régions afin de pouvoir réaliser une comparaison des régions avec et sans intervention. Enfin en 2010, un réseau clinique et anatomo-pathologique sera implémenté en France (Inca) et les  résultats de cette étude permettront d'apporter des éléments importats pour la mise en place d'actions nationales pour la prise en charge des STM.